THE VALIDITY OF THE NOTARY DEED TO REVIEW A TYPE OF ERROR USING A PEN ERASER - Yossi Islamiya Pratiwi; Hamzah Halim; Nurfaidah Said (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The authority of a notary is governed by the Notary Position Act in article 15 paragraph (1). In terms of erasing using a pen eraser, is not allowed and is not regulated in the Notary Position Act. However, if the minutes and copies of the deed remain the same, then the error in the deed is not a substantive error and there is no lawsuit against it. Therefore, the deed is still valid as an authentic deed. Regarding the legal consequences, whether a Notary deed is an authentic deed or not, will be decided by a judge in court.